Layer ensemble averaging for fault tolerance in memristive neural networks - Osama Yousuf; Brian D. Hoskins; Karthick Ramu; Mitchell Fream; William A. Borders; Advait Madhavan; Matthew W. Daniels; Andrew Dienstfrey; Jabez J. McClelland; Martin Lueker-Boden; Gina C. Adam (Nature Communications)
Abstract Artificial neural networks have advanced due to scaling dimensions, but conventional computing struggles with inefficiencies due to memory bottlenecks. In-memory computing architectures using memristor devices offer promise but face challenges due to hardware non-idealities. This work proposes layer ensemble averaging—a hardware-oriented fault tolerance scheme for improving inference performance of non-ideal memristive neural networks programmed with pre-trained solutions. Simulations on an image classification task and hardware experiments on a continual learning problem with a custom 20,000-device prototyping platform show significant performance gains, outperforming prior methods at similar redundancy levels and overheads. For the image classification task with 20% stuck-at faults, accuracy improves from 40% to 89.6% (within 5% of baseline), and for the continual learning problem, accuracy improves from 55% to 71% (within 1% of baseline). The proposed scheme is broadly applicable to accelerators based on a variety of different non-volatile device technologies.